Early mesodermal development in the patellogastropod Lottia goshimai. (14th April 2022) - Sun, Dehui; Huan, Pin; Liu, Baozhong
Abstract: Mesodermal development is essential to explore the interlineage variations in the development of spiralians. Compared with model mollusks such as Tritia and Crepidula, knowledge about the mesodermal development of other molluscan lineages is limited. Here, we investigated early mesodermal development in the patellogastropod Lottia goshimai, which shows equal cleavage and has a trochophore larva. The endomesoderm derived from the 4d blastomere, that is, the mesodermal bandlets, was situated dorsally and showed a characteristic morphology. Investigations of the potential mesodermal patterning genes revealed that twist1 and snail1 were expressed in a proportion of these endomesodermal tissues, while all of the five genes we investigated ( twist1, twist2, snail1, snail2, and mox ) were expressed in ventrally located ectomesodermal tissues. Relatively dynamic snail2 expression suggests additional roles in various internalization processes. By tracing snail2 expression in early gastrulae, the 3a 211 and 3b 211 blastomeres were suggested to be the precursors of the ectomesoderm, which elongated to become internalized before division. These results help to understand the variations in the mesodermal development of different spiralians and explore the different mechanisms by which ectomesodermal cells are internalized, which has important evolutionary implications.